Emergence of drug resistance‐associated variants and changes in serum lipid profiles in sofosbuvir plus ledipasvir‐treated chronic hepatitis C patients. Issue 11 (25th July 2017) - Kan, Hiromi; Imamura, Michio; Kawakami, Yoshiiku; Daijo, Kana; Teraoka, Yuji; Honda, Fumi; Nakamura, Yuki; Morio, Kei; Kobayashi, Tomoki; Nakahara, Takashi; Nagaoki, Yuko; Kawaoka, Tomokazu; et al.
Abstract : Combination of sofosbuvir plus ledipasvir therapy has been expected to enhance sustained virological response (SVR) rates in hepatitis C virus (HCV) genotype 1 chronic infected patients. We analyzed the emergence of drug resistance‐associated variants (RAVs) in treatment failure and changes in lipid profiles in sofosbuvir/ledipasvir‐treated patients. A total of 176 patients with chronic HCV genotype 1 infection without decompensated liver cirrhosis were treated with sofosbuvir/ledipasvir for 12 weeks. NS5A and NS5B RAVs were determined by either Invader assay or direct sequencing. Serum lipid‐related markers were measured at the start of treatment and at week 4 in patients who received sofosbuvir/ledipasvir and ombitasvir/paritaprevir/ritonavir therapies. SVR was achieved in 94.9% (167 out of 176) of patients. SVR12 rate was 97.1% for patietns with low frequncy (<25%) of baseline NS5A RAVs, but 82.8% for patients with high frequency (>75%) of NS5A RAVs. In multivariate regression analysis, higher albumin (odds ratio [OR] = 0.020 for presence; P = 0.007), and NS5A‐L31/Y93 RAVs with a population frequency <75% (OR = 29.860 for presence; P = 0.023) were identified as significant independent predictors for SVR12. NS5A‐Y93H substitutions were detected in all nine treatment failures at HCV relapse, and three out of six patients with NS5A inhibitor‐naïve patients achieved additional NS5A RAVs. Serum low‐density lipoprotein cholesterol and apolipoprotein B levels were significantly elevated at week 4 in sofosbuvir/ledipasvir‐treated patients. These elevations were greater than in ombitasvir/paritaprevir/ritonavir‐treated patients. In conclusion, NS5A multi‐RAVs are likely to develop in patients who fail to respond to sofosbuvir/ledipasvir therapy. Inhibition of HCV replication with sofosbuvir might affect lipid metabolism.